1999
DOI: 10.1161/01.atv.19.3.762
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serotonin Receptor Density and Platelet GPIIb/IIIa Activation Among Smokers

Abstract: Abstract-This study sought to determine whether depressive symptoms and/or platelet serotonin receptor (5HT 2A ) density are associated with increased platelet activation (PA) found among smokers. Flow cytometric detection of PA was used to study 36 smokers and 16 nonsmokers, aged 18 to 48 years. Subjects were tested at baseline and after either smoking 2 cigarettes (smokers) or a similar resting interval (nonsmokers). Assessment of PA included both platelet secretion and fibrinogen receptor (GPIIb/IIIa) bindi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…In a recent study, Steckler et al (1993) Our results should be interpreted with caution. Smoking (Markovitz et al 1999) and progesterone or estrogen (for review, see Berendsen 2000) have been shown to cause changes in 5HT 2A receptors. We did not have adequate information on the patients' smoking history, and the stages of the menstrual cycle in female patients, and hence we cannot exclude the possibility that the increases in 5HT 2A receptors in our BP or SA patients may be related to these factors.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Steckler et al (1993) Our results should be interpreted with caution. Smoking (Markovitz et al 1999) and progesterone or estrogen (for review, see Berendsen 2000) have been shown to cause changes in 5HT 2A receptors. We did not have adequate information on the patients' smoking history, and the stages of the menstrual cycle in female patients, and hence we cannot exclude the possibility that the increases in 5HT 2A receptors in our BP or SA patients may be related to these factors.…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoking is strongly associated with MI in our population, and smokers are likely to have an increased platelet 5-HT #A receptor density [5]. First, we analysed a limited number of patients and control subjects.…”
Section: Discussionmentioning
confidence: 99%
“…the identification of individuals particularly likely to benefit from glycoprotein IIb/IIIa inhibitor therapy). Cigarette smoking is associated with increased glycoprotein IIb/IIIa receptor activation (Markovitz et al , 1999), as well as with increased circulating levels of fibrinogen (Folsom, 1999), the ligand that binds to glycoprotein IIb/IIIa. These findings provide possible mechanisms underlying the synergism we observed between the genetic variant of platelet glycoprotein IIb and smoking in the pathogenesis of acute MI.…”
Section: Discussionmentioning
confidence: 99%